A portable and multifunction tracker - Wong, Adam Wei Jiang (2021)
In this century, people always travel and lack of financial literacy. In order to solve the problem, this project included both functions, tracking system with NFC tags and money managing system 2 in 1. The traditional trackers come with a lot of disadvantages that is already outdated in this century. With the help of technology, this project can be done within Android Studio with Java language. The methodology that used in this project is Rapid Application Development. This project is going to research in the pros and cons of similar system and will try to implement anything that suitable for this project. The goal of this project is to help Amnesia patients to keep their record of trace also helps kids who are 7 years old and above to have a good habit of financial. This project will be more focus on UI design and user experience. In order to attract the attention form kids, this project do some research for the theme, font, and color. Besides, this application also including the Mysejahtera function with the NFC tags to fulfill those who really sensitive to their privacy and personal information.